36. THE KNOWLEDGE AND BEHAVIORS AMONGST OLDER ADULTS WITH HYPERTENSION: A QUALITATIVE INVESTIGATION IN DA TON COMMUNE, GIA LAM DISTRICT, HANOI (Vietnam Journal of Community Medicine, 2024)
Objective: The study aims to explore the experiences of older adults in Da Ton Commune, Gia Lam, Hanoi regarding their knowledge and behaviors in managing hypertension.Materials and methods: The study employs qualitative research methods and in-depth interviews. The participants in the study included hypertensive older adults ( 60 years old) and the primary caregivers of older adults.Result: The study revealed significant disparities among the participants in terms of their knowledge and behaviors related to managing hypertension. While over 85% of the participants demonstrated a sufficient understanding of hypertension, their actual behaviors did not align with their knowledge. Undesirable behaviors included seeking medical attention only when experiencing severe symptoms, a lack of proactive adjustment in dietary habits, limited initiative in researching their prescribed medications, and a failure to consistently monitor their blood pressure levels. Furthermore, the health information resources aimed at the elderly population lack the necessary diversity and effectiveness to improve their healthcare management skills.Conclusion: The research findings suggest that the elderly population in Da Ton Commune possesses a rudimentary understanding of hypertension. However, their knowledge is not comprehensive enough to induce them to voluntarily modify their behaviors and lifestyles. It is vital to enhance their knowledge through educational interventions and provide instructions on the importance of adherence behavior while making credible sources of information available to them. Thus, it will enhance their quality of life and contribute to a more sustainable community.
Keywords: Hypertension, Older Adults, Qualitative study.